A stationary long-pulse ELM-absent H-mode regime in EAST. (14th July 2017) - Ye, Y.; Xu, G.S.; Wan, B.N.; Chen, R.; Yan, N.; Guo, H.Y.; Shao, L.M.; Yang, Q.Q.; Wang, H.Q.; Zhang, W.; Xia, T.Y.; Zhang, T.; et al.
Abstract: A stationary edge-localized mode (ELM)-absent H-mode regime, with an electrostatic edge coherent mode (ECM) which resides in the pedestal region, has been achieved in the EAST tokamak recently. This regime allows the operation of a nearly fully noninductive long pulse (>15 s), exhibiting a relatively high pedestal and good global energy confinement with H 98, y 2 near 1.2, and excellent impurity control. Furthermore, this regime is mostly obtained with a 4.6 GHz lower hybrid current drive (LHCD) or counter-current neutral beam injection (NBI), plus electron cyclotron resonance heating, and an extensive lithium wall coating. This stationary ELM-absent H-mode regime transits to a stationary small ELM H-mode regime, and upon additional heating power from the 2.45 GHz LHCD, an ion cyclotron resonant frequency or co-current NBI is applied (under 4.6 GHz LHCD heating background). A slight change of the plasma configuration also makes the small ELMs reappear. The experimental observations suggest that a long-pulse ELM-absent regime can be induced by the ECM, which exhibits strong electrostatic fluctuations and may provide a channel for continuous particle (especially impurities) and heat exhaust across the pedestal. The ECM exists in the collisionality of ν e ∗ = 2.5–4 and the pressure gradient | ∇ P | = | d P ​ ​ ╱ ​ ​ d ρ | = 100–200 (kPa), which is in good agreement with the previous simulation of GYRO. This ELM-absent H-mode regime with ECM may offer a suitable candidate for high-performance, steady-state H-mode operation in future fusion reactors.